CURRICULUM HISTORY AND PLANNING: THEORETICAL FRAMEWORK AND SOME GUIDELINES OF ITS DEVELOPMENT IN ESTONIA, 1987–1996 - Rouk, Vadim (Acta Paedagogica Vilnensia, 2013)
The reform of the national school curriculum in Estonia began after the Teacher’s Congress in 1987 and ended in 1996 when the government approved the document. The reform was carried out in the context of thoroughgoing and dramatic historical changes that deeply affected the whole Estonian society. The aim of the paper is to position the example of Estonian curricular development into a broader international, theoretical, and historical context. Some similarities and differences of curriculum history in Great Britain and Latvia are also discussed.